Assessing the sustainability and cost-effectiveness of concrete incorporating various fineness of eggshell powder as supplementary cementitious material - Jhatial, A.A. (Springer Science and Business Media Deutschland GmbH, 2022)
The eggshell powder (ESP) has been used as a partial cement replacement to reduce the cement content in concrete production. According to recent estimates, cement production contributes to 7 of global Carbon Dioxide (CO2) gas emissions. However, most of the studies so far have focused on the mechanical strength aspect of the concrete incorporating ESP; however, there is a lack of information on the influence of ESP on the sustainability of concrete in terms of embodied carbon and eco-strength efficiency. Therefore, this study aims at determining the influence of ESP on the sustainability and cost of an M40 grade concrete when different fineness ESP (50Â Âµm and 100Â Âµm) is utilized as partial cement replacement. The sustainability was assessed in terms of embodied carbon and eco-strength efficiency, while the cost-effectiveness was determined in terms of the overall cost of concrete and cost to produce unit compressive strength. It was observed that the control M40 concrete mix achieved a total embodied carbon of 482.88 kgCO2/m3. With 5 to 15 ESP of 100Â Âµm fineness, the total embodied carbon was successfully reduced, ranging from 3.86 to 11.60. While 5 to 15 of 50Â Âµm fineness, the reduction ranged from 3.69 to 11.10. The 50Â Âµm fineness ESP exhibited slightly lower eco-strength efficiency compared to 100Â Âµm fineness ESP; however, both achieved relatively higher eco-strength efficiency. In terms of cost, the inclusion of ESP resulted in a significant reduction in overall cost and was cheaper to produce 1Â MPa compressive strength. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.